2020
DOI: 10.1371/journal.pone.0244389
|View full text |Cite
|
Sign up to set email alerts
|

The impact of service-learning methodology on business schools’ students worldwide: A systematic literature review

Abstract: The purpose of this research is to perform a systematic review of the literature published on the benefits of applying the service-learning methodology with business students. Several works and studies identify significant contributions that are important to the student’s profile; however, a systematic review of the benefits derived from the methodology application in the profile previously described has not yet been conducted. The main objective of this study is to gather, identify, and classify evidence from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 53 publications
(35 reference statements)
1
16
0
3
Order By: Relevance
“…Results clearly indicated that interactions with the innovators led to student experiences of increased critical awareness about social problems, adoption of transdisciplinary communityserving approaches to address such problems and strengthened self-confidence in one's capacity to make a difference. While similar student experiences have been noticed in a range of other studies on service-learning (Marco-Gardoqui et al, 2020;Myers, 2020), our findings add a new perspective by focusing on master's students from a gender perspective. Female students especially reported that they now felt more confident in carrying out social innovation themselves.…”
Section: Gendered Experiences With the Workhopsupporting
confidence: 87%
See 2 more Smart Citations
“…Results clearly indicated that interactions with the innovators led to student experiences of increased critical awareness about social problems, adoption of transdisciplinary communityserving approaches to address such problems and strengthened self-confidence in one's capacity to make a difference. While similar student experiences have been noticed in a range of other studies on service-learning (Marco-Gardoqui et al, 2020;Myers, 2020), our findings add a new perspective by focusing on master's students from a gender perspective. Female students especially reported that they now felt more confident in carrying out social innovation themselves.…”
Section: Gendered Experiences With the Workhopsupporting
confidence: 87%
“…Through the aforementioned study design, we combined two established approaches that often occur in outcome-oriented research on service-learning: pretest–posttest design based on scales and questionnaires (Eidson et al , 2018); and research based on mixed methods (usually applied without a longitudinal design) (Marco-Gardoqui et al , 2020). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, there is a broad consensus (Butin 2010;Puig 2009; Speck and Hoppe 2004) on the need to identify S-L methodology as an educational methodology that challenges traditional pedagogical discourses; a methodology that expands the scope of teaching activity beyond the classroom (Wang et al 2020), generates spaces for the development of social engagement (Marco-Gardoqui et al 2020) and ethical behaviours (Lee et al 2020), promotes autonomy, self-efficacy (Gerholz 2017), engagement (Folgueiras et al 2018) and critical thinking (Kuntjara 2019), generates satisfaction with the learning achieved (Lorenzo-Moledo et al 2021), and facilitates meaningful learning (Celio et al 2011). This methodology "is based on the idea that mutual assistance is a better mechanism for personal, economic, and social progress than competition and the obsessive pursuit of success" (Puig 2009: 10).…”
Section: S-l Methodology: Key Coordinatesmentioning
confidence: 99%
“…The benefits of SL across studies are mostly divided into two categories – personal and professional. For instance, Marco-Gardoqui et al . (2020) summarised nine benefits of SL through a systematic review on similar lines.…”
Section: Literature Reviewmentioning
confidence: 99%